(996) Analysis of Data on Fertility, Mortality and Economic Activity of Urban Population in Libya Based on a Household Sample Survey تحليل البيانات المتعلقة بالمواليد والوفيات والنشاط الاقتصادي لسكان الحضر في ليبيا استناداً إلى مسح لعينة من الأسر . - Soliman Nour Eldin. (INP, 2025)
30 P